2019
DOI: 10.1039/c9lc00149b
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a high-throughput droplet sorter

Abstract: The high-throughput selection of individual droplets is an essential function in droplet-based microfluidics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…At the same time, in the case of several biomedical applications, the fluorescence staining of cells can affect their behavior and thereby compromising their potential clinical implementation, therefore, it can be favorable if the cells get sorted in their native state. Based on the microfluidic design principles developed for fluorescence‐activated droplet sorting, [ 16,17 ] we set out to use the physical parameters obtained by the developed optical device for real‐time, label‐free droplet sorting. Toward this end, a combination of parameters including the SSD and the binarized size (yellow polygon in Figure 4B) was chosen to trigger the separation of cell‐laden droplets from empty droplets (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, in the case of several biomedical applications, the fluorescence staining of cells can affect their behavior and thereby compromising their potential clinical implementation, therefore, it can be favorable if the cells get sorted in their native state. Based on the microfluidic design principles developed for fluorescence‐activated droplet sorting, [ 16,17 ] we set out to use the physical parameters obtained by the developed optical device for real‐time, label‐free droplet sorting. Toward this end, a combination of parameters including the SSD and the binarized size (yellow polygon in Figure 4B) was chosen to trigger the separation of cell‐laden droplets from empty droplets (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Using a machine learning approach, the manual selection of the parameter space will be further facilitated and automated. With a potent and optimized microfluidic setup, [17,18] the maximum achievable analysis rate of 10 000 Hz roughly leads to a theoretical sorting capacity of >3000 droplets/s. In addition to identification of cellloaded droplets, a proper selection of analyzed parameters will enable classification of the cells inside the droplet, for example by their size, morphology, or stage.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate channels loaded with a concentrated salt solution, and located adjacent to the sorting junction were responsible for inducing a dielectrophoretic force, required for sorting, on the droplet. 39,40 The sorting channel then led to a storage line having a high depth so that droplets decelerated and approximately 30 of the last sorted droplets could be stored in the sequence they were sorted ( Fig. 1A-4).…”
Section: A Monolithic Microfluidic Device For Droplet Generation MIXmentioning
confidence: 99%
“…A maximum of only 20 min incubation was required, and spike‐in experiments (with a target cell:WBC ratio of as little as 10:200 000) showed that the detection rate was ≈60%. Given that there are many powerful droplet sorting platforms, one could also make use of these for collecting the acidified droplets for further analysis.…”
Section: Detecting Biomarkers For Cancer Diagnosis and Stratificationmentioning
confidence: 99%